2011
DOI: 10.1021/ja205106e
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Groups of Trimethylamine N-Oxide Orient Away from Hydrophobic Interfaces

Abstract: The molecular orientation of trimethylamine N-oxide (TMAO), a powerful protein stabilizer, was explored at aqueous/hydrophobic interfaces using vibrational sum frequency spectroscopy (VSFS). The systems studied included the octadecyltrichlorosilane (OTS)/water interface, which represents an aqueous solution in direct contact with a hydrophobic medium. Surprisingly, the measurements revealed that the methyl groups of TMAO pointed into the aqueous phase and away from the OTS. This orientation may arise from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 67 publications
9
82
0
Order By: Relevance
“…Urea has a hydration shell spanning 1.3 Å [at g(r) = 1], whereas TMAO has a hydration shell spanning 1.9 Å. Moreover, TMAO has been reported to stabilize native peptide states by acting as a molecular crowder (15,17), as well as by virtue of being depleted from the surface as the protein adopts its native state (18,19). Our earlier computational studies on bulk TMAO showed that the osmolyte's methyl groups did not act as conventional hydrophobic moieties, in agreement with the experiments of Sagle (18), which demonstrated that the methyl groups of TMAO oriented away from hydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Urea has a hydration shell spanning 1.3 Å [at g(r) = 1], whereas TMAO has a hydration shell spanning 1.9 Å. Moreover, TMAO has been reported to stabilize native peptide states by acting as a molecular crowder (15,17), as well as by virtue of being depleted from the surface as the protein adopts its native state (18,19). Our earlier computational studies on bulk TMAO showed that the osmolyte's methyl groups did not act as conventional hydrophobic moieties, in agreement with the experiments of Sagle (18), which demonstrated that the methyl groups of TMAO oriented away from hydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of decyldimethylamine N-oxide (DDAO) surfactant dramatically decreases the surface tension of the water, 107 whereas adding trimethylamine N-oxide (TMAO) molecule to water modestly increases the surface tension. 108 Moreover, the addition of tetraphenylarsonium (Ph 4 As + ) and tetraphenylborate (Ph 4 B -) ions to water, which have similar molecular sizes, structures, and masses, but opposite sign of charge, reduces the surface tension at the water-oil interface in a different manner; the surface tension of the water-oil interface is ~15 % larger for the Ph 4 B -aqueous solution than for the Ph 4 As + solution, when the ion concentration in the bulk is the same. 109 Unveiling the molecular- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27 level physics underlying the surface tensions provide a route to the optimal design rules for controlling surface activities.…”
Section: A Interplay Of Complex Ions At Aqueous Interfacesmentioning
confidence: 99%
“…Thus, it was proposed that protein destabilization by TMAO at low pH is caused a preferred osmolyte binding to the protein surface [54]. There are a number of publications where authors suggest that polar groups of osmoprotectors can bind to the protein backbone chain, while practically not interacting with hydrophobic residues and side chains [8,[56][57][58][59]. It should be noted, however, that based on [60], the denaturing osmolyte urea can interact with hydrophobic residues of a protein chain.…”
Section: Osmolytes Of Class II Increase (mentioning
confidence: 99%